Bioprospecção de bactérias promotoras do crescimento de plantas na microbiota endofítica de Mimosa tenuiflora (Willd) Poir - Andrade, João Victor Teixeira de (2024)
Mimosa tenuiflora is a pioneer plant found in desertified areas of the Brazilian semi-arid region, where it plays a fundamental role in the ecological succession of the Caatinga biome. Despite the relevance of endophytic bacteria for plant development and health, knowledge about this community in this plant still has several gaps. This study, in this sense, aimed to isolate and characterize plant growth-promoting bacteria (PGPB) from the endophytic community of M. tenuiflora with the purpose of obtaining a consortium of PGBP to accelerate the restoration of degraded areas of the Caatinga. To this end, roots were collected in native areas of the Caatinga (RN), areas undergoing natural recovery from 23 years of overgrazing (RR) and areas in a critical stage of desertification (RD). The roots were macerated in saline solution, diluted and inoculated in different nutritional media. The isolates were characterized and tested to produce indole acetic acid, ammonia, siderophores and exopolysaccharides, as well as for the solubilization of potassium and inorganic phosphate. In total, 86 isolates were found, with 22, 28 and 36 coming from RD, RN and RR, respectively. All isolates were positive for at least one plant growth- promoting activity. Ammonia, siderophores and exopolysaccharides stand out as the most conserved activities. Potassium solubilization was only observed in RN bacteria. Furthermore, it was possible to verify that PGPB from areas RD and RR included fewer functional activities, compared to isolates from areas RN. Nine strains of PGPB, comprising Proteobacteria and Actinobacteria, were selected as promising for the development of native bioinoculants to accelerate the ecological succession of degraded areas in the Brazilian semi-arid region. From molecular identification with the 16S rRNA gene, it was observed that all promising isolates illustrate species associated with promoting plant growth in environments marked by adverse abiotic conditions, such as salinity, water stress and metal contamination.